Patterns of antibiotic administration in Chinese neonates: results from a multi-center, point prevalence survey - Jiaosheng Zhang; Li Lin; Gen Lu; Keye Wu; Daiyin Tian; Lanfang Tang; Xiang Ma; Yajuan Wang; Gang Liu; Yanqi Li; Jing Qian; Ping Wang; et al. (BMC Infectious Diseases, 2024)
Abstract Objectives In this study, we describe the patterns of antibiotic prescription for neonates based on World Health Organization’s (WHO) Essential Medicines List Access, Watch, and Reserve (AWaRe), and the Management of Antibiotic Classification (MAC) Guidelines in China. Methods One-day point-prevalence surveys (PPS) on antimicrobial prescriptions were conducted on behalf of hospitalized neonates in China from September 1 and November 30, annually from 2017 to 2019. Results Data was collected for a total of 2674 neonatal patients from 15 hospitals in 9 provinces across China of which 1520 were newborns who received at least one antibiotic agent. A total of 1943 antibiotic prescriptions were included in the analysis. The most commonly prescribed antibiotic was meropenem (11.8%). The most common reason for prescribing antibiotic to neonates was pneumonia (44.2%). There were 419 (21.6%), 1343 (69.1%) and 6 (0.3%) antibiotic prescriptions in the Access, Watch and Reserve groups, respectively. According to MAC Guidelines in China, there were 1090 (56.1%) antibiotic agents in the Restricted and 414 (21.3%) in the Special group. Conclusion Broad-spectrum antibiotics included in the Watch and Special groups were likely to be overused in Chinese neonates.